Extracorporeal Membrane Oxygenation in Children With Cancer or Hematopoietic Cell Transplantation: Single-Center Experience in 20 Consecutive Patients - Potratz, Jenny C.; Guddorf, Sarah; Ahlmann, Martina; Tekaat, Maria; Rossig, Claudia; Omran, Heymut; Masjosthusmann, Katja; Groll, Andreas H. (Frontiers in Oncology, 2021)
Extracorporeal membrane oxygenation (ECMO) is a rescue therapy for severe respiratory and/or circulatory failure. Few data exist on the potential benefit of ECMO in immunocompromised pediatric patients with cancer and/or hematopoietic cell transplantation (HCT). Over a period of 12 years, eleven (1.9%) of 572 patients with new diagnosis of leukemia/lymphoma and nine (3.5%) of 257 patients post allogeneic HCT underwent ECMO at our center. Five (45%) and two (22%) patients, respectively, survived to hospital discharge with a median event-free survival of 4.2 years. Experiences and outcomes in this cohort may aid clinicians and families when considering ECMO for individual patients.